Physical Activity, Bipolar Disorder and Me - Andrea , C. Lindsay (International Journal of Psychosocial Rehabilitation, 2014)
Topic: Since individuals with BD are at higher risk of morbidity than the average population, physical activity as a treat- ment option needs more attention.Purpose: To make recommendations about physical activity and the client with bipolar disorder; a discussion aimed primarily to health care providers.Sources Used: This paper combines both references to published research and a first person narrative.Conclusions and Implications for Practice: Discussion begins by looking at the cost and incidence of the co-morbidities in people with bipolar disorder. Physical activity as a treatment option is reviewed. The benefits of physical activity are listed and examined. It is cost-effective for society as a whole to focus on supporting individuals in physical activity, as it may reduce hospital admissions. Numerous obstacles facing clients with BD are discussed. The role of health care work- ers in promoting physical activity is discussed. Specific obstacles in an institutional setting are briefly examined. Mental health caregivers need to include physical activity in treatment planning. While physical activity is at the discretion of the individual, any form of physical activity is beneficial.